Validation of the Arabic version of the Gratitude Questionnaire (GQ-4) in a sample of non-clinical adults - Feten Fekih-Romdhane; Álvaro Postigo; Diana Malaeb; Abir Sarray El Dine; Mira Moawad; Rabih Hallit; Sahar Obeid; Souheil Hallit (BMC Psychology)
Abstract Background Although gratitude is a culturally-sensitive construct, it has yet received limited research attention in Arab countries, hence hindering the understanding of its features, correlates, and cross-cultural specificities. To fill this gap, we sought to examine the psychometric properties of an Arabic translation of the 6-item Gratitude Questionnaire (GQ) in an Arabic-speaking sample of adults from the general population of Lebanon. Method We conducted a web-based survey including 601 participants (mean age 29.91 ± 12.61, 62.7% females). The forward-backward translation method was used for the translation and adaptation of the GQ-6 into the Arabic language. Results Findings indicated that a four-item version of the GQ achieved adequate fit statistics with the removal of the two reverse-scored third and sixth items. We found a McDonald Omega coefficient for the total 4-item GQ (GQ-4) scores of 0.88, thus attesting for the good reliability of the scale. Multiple-group Confirmatory Factor Analysis showed that the scale structure was invariant across male and female respondents at the configural, metric, and scalar levels. Females exhibited significantly higher gratitude scores compared to males. Finally, discriminant validity of the Arabic GQ-4 was evidenced through positive significant correlations with social support levels. Conclusion The Arabic adaptation of the GQ showed good psychometric qualities, suggesting that it is suitable for measuring people’s disposition toward gratitude in Arab backgrounds. Offering the Arabic GQ-4 as a brief, simple, cost-effective, valid, and reliable measure of gratitude to the Arabic-speaking community could help raise awareness about gratitude as a key component for achieving good mental health and wellbeing in Arab contexts.